Organisational Agility and 7Ps of the marketing mix for the post-COVID-19 period: A case study of the Indian informal food sector - Ramkumar, Uma Vakadae; Raja, Manivannan Anand Shankar; Kureethara, Joseph Varghese (The journal of contemporary issues in business and government, 2021)
This study uncovers the reality of the COVID-19 epidemic, acting as a significant hurdle for small restaurants' sustainability.The study used a purely qualitative methodology dealing with data collected from the industry to frame effective sustainability strategies to revamp the business.Hence,in-depth interviews to capture the real problems faced by restaurants were conducted.From the study, we understood that big citiessuch asChennai, Bengaluru and Thiruvananthapuram took initiatives in the post-COVID-19 crisis to bring about changes in the business process, giving importance to online ordering and delivery, new cuisines and more hygienic transparency. Small cities such as Coimbatore, Thiruvallaand Kochi are still confident of running their businesses, but there may not be a drastic change in the process. However, their expectations of help from the government are high. Three major factors are being considered to be cornerstone elements, which are health, cleanliness and hygiene. In this research, the scope is limited only to restaurants in big and small cities, whilelarge-sized star category hotels have not been considered.